Descartes e o ceticismo : um exame da controvérsia entre Popkin e Lennon - Ana Cláudia Teodoro Sousa (2020)
The aim of this work is to compare two contemporary interpretations of how Cartesian philosophy is linked with skepticism and thus to establish whether Descartes aimed to responding and eliminating skepticism; if so, we will indicate how he would have accomplished this task and then determine whether or not he would have been successful within this possible endeavor, also pointing to the consequences if the answer reveals a failed attempt. First, we return to Richard Popkin's groundbreaking reading of Cartesian philosophy, which places it within the context of a Pyrrhonian crisis of modernity, establishing that Descartes' solution to his own hyperbolic methodological doubt is not merely an epistemic work internal to his philosophy, but it also appears as a reaction to the Pyrrhonian crisis. Popkin understands that Cartesian philosophy has as its main goal to answer the skeptical arguments, but fails in this endeavor, which would make Descartes a skeptic malgré lui. Subsequently, we present Thomas Lennon's reading, antagonistic to Popkin’s, which claims that Cartesian philosophy was not meant to respond to skepticism and that, despite having done so, failing to do something that was not set as a goal would not be a problem, at least not as major as Popkin says. Thus, by analyzing the sources presented by these two authors and seeking contextual and historical information about the passages of the Cartesian corpus that indicate the relation of this philosophy with skepticism, we point out the forces that emerge from the readings of Popkin and Lennon, also showing where they fail. In this sense, we recognize that it is not possible to overlook the importance of skepticism among Cartesian’s influences, but neither it is possible to exaggerate by saying that refuting skepticism was the main purpose of Descartes’ philosophy. Furthermore, we find that Descartes cannot be a skeptic despite his dogmatic intentions, as Popkin indicates, even though Cartesian philosophy has reinforced the difficulty that skepticism posed after having its foundations questioned by the very skeptical doubts that are the starting point of this philosophy.